2013
DOI: 10.1007/s00203-013-0919-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pesticides on bacterial nitrogen fixers in peanut-growing area

Abstract: In the peanut production, the applications of herbicides and fungicides are a common practice. In this work, studies done under field conditions demonstrated that pesticides affected negatively the number and nitrogenase activity of diazotrophic populations of soil. Agrochemical effects were not transient, since these parameters were not recovered to pre-treatment levels even 1 year after pesticides application. Results obtained from greenhouse experiments revealed that the addition of herbicide or fungicides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…Khan et al (2006) also recorded a reduction of nitrogenase activity after the pre-emergent application of methabenzthiazuron (MBT), terbutryn, and linuron to chickpea cultivation. Similar results were noted by Angelini et al (2013), who revealed a negative effect of a series of active ingredients (including s-metolachlor) on the diazotrophic bacterial community and soil nitrogenase activity. Moreover, they also noted a prolonged negative effect on the next culture, even at one year after application.…”
Section: Nitrogen Fixationsupporting
confidence: 88%
See 1 more Smart Citation
“…Khan et al (2006) also recorded a reduction of nitrogenase activity after the pre-emergent application of methabenzthiazuron (MBT), terbutryn, and linuron to chickpea cultivation. Similar results were noted by Angelini et al (2013), who revealed a negative effect of a series of active ingredients (including s-metolachlor) on the diazotrophic bacterial community and soil nitrogenase activity. Moreover, they also noted a prolonged negative effect on the next culture, even at one year after application.…”
Section: Nitrogen Fixationsupporting
confidence: 88%
“…The cultivation of leguminous plants has a wide range of advantages, including the production of atmospheric nitrogen, the recovery of nutrients washed out into deeper soil layers by means of the long root system, improvement of the soil structure by leaving air tracts, and increasing the sorption capacity of the soil complex and the content of humus by leaving a large mass of crop residues (Galbally et al 2010). Soil nitrogen-fixing bacteria play an important role in leguminous plant productivity (Angelini et al 2013) as well as for other crops. In spite of many advantages of leguminous plants, there is not much interest in the production of these species in Poland, as the area where these crops are sown amounts to only 1% of the total crop area (GUS 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the application of agrochemicals (fertilizers and pesticides) can change soil properties and microbial community structure. Estimates indicate that only 0.1 % of the applied pesticides reach the target pests, with the remaining 99.9 % accumulating in the soils and directly or indirectly affecting the microbial density and enzymatic activities (Singh and Singh, 2005;Das and Debnath, 2006;Pal et al, 2006;Angelini et al, 2013). The addition of pesticides to agricultural soils has been reported to negatively affect the bacterial population of nitrogen fixers (Angelini et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates indicate that only 0.1 % of the applied pesticides reach the target pests, with the remaining 99.9 % accumulating in the soils and directly or indirectly affecting the microbial density and enzymatic activities (Singh and Singh, 2005;Das and Debnath, 2006;Pal et al, 2006;Angelini et al, 2013). The addition of pesticides to agricultural soils has been reported to negatively affect the bacterial population of nitrogen fixers (Angelini et al, 2013). Similarly, soil microbial communities are known to be highly influenced by management practices, and they may be reduced by the application of inorganic fertilizers and pesticides during cultivation (Moeskops et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have analyzed diversity of nif genes encoding the bacterial enzyme nitrogenase (Ladha and Reddy, 2003;Mártensson et al, 2009). In this sense, in a previous study, Angelini et al (2013) observed that pesticides application decrease the abundance and diversity of nitrogen-fixing bacteria from soil DNA extracts from peanut-growing area of Córdoba. The present study would be the first one that addresses the analysis of "representative" genes from a subpopulation of bacteria able to P solubilization.…”
Section: Effect Of Pesticides On the Diversity Of Soil Bacterial Commmentioning
confidence: 98%